Evaluation of Clove Volatile Extract Vaporizer Mats for Mosquito Control Against Aedes aegypti: Bioassay and Computational Analysis - Mochammad Aqilah Herdiansyah; Rifaid Nur Arsad; Rosalia Nuril Qolbi; Inge Permatasari; Etik Ainun Rohmah; Sri Subekti; Siti Fatimatuz Zahra; Kris Cahyo Mulyatno; Intan Ayu Pratiwi; Zubaidah Ya’cob; Win Darmanto (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2026)
Syzygium aromaticum contains bioactive compounds that may serve as natural alternatives to synthetic mosquito control agents. This study aimed to evaluate the mosquitocidal activity of stem, leaf, and bud extracts of S. aromaticum, formulated as vaporizer mats, against Aedes aegypti and to identify potential molecular targets of the major compounds in these extracts through computational analysis. Volatile extracts from stems, leaves, and buds were prepared by ethanol maceration and formulated into vaporizer mats at concentrations of 0.5% and 1%. A total of 525 adult A. aegypti (F330 strain) were exposed under controlled laboratory conditions in accordance with WHO guidelines. Mortality, LT50, and LT90 values were recorded after exposure. Molecular docking was performed against odorant-binding protein AaegOBP1 and pyruvate kinase (PK1), followed by molecular dynamics simulation. Among all treatments, bud extract at 1% produced the highest mortality (33%), compared with 2% in the negative control. LT50 and LT90 values for this treatment were 1.468 minutes and 50.543 minutes, respectively, indicating prolonged biological activity. Docking analysis showed that β-caryophyllene had the strongest affinity toward AaegOBP1 (-8.4 kcal/mol), while chavicol showed the strongest interaction with PK1 (-6.5 kcal/mol). Molecular dynamics simulation confirmed stable ligand-receptor interactions with RMSF values below 3 Å. These findings indicate that S. aromaticum bud extract has moderate mosquitocidal potential in vaporizer mat formulation and may act through olfactory disruption and metabolic interference in A. aegypti.